1995
DOI: 10.1097/00000539-199505000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Prone Positioning During General Anesthesia Minimally Affects Respiratory Mechanics While Improving Functional Residual Capacity and Increasing Oxygen Tension

Abstract: We investigated the effects of the prone position on the mechanical properties (compliance and resistance) of the total respiratory system, the lung, and the chest wall, and the functional residual capacity (FRC) and gas exchange in 17 normal, anesthetized, and paralyzed patients undergoing elective surgery. We used the esophageal balloon technique together with rapid airway occlusions during constant inspiratory flow to partition the mechanics of the respiratory system into its pulmonary and chest wall compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 17 publications
2
47
2
4
Order By: Relevance
“…Although it has been reported that patients in the prone position were better oxygenated than those in the supine position, during general anesthesia [7], our patient experienced low oxygenation in the prone position on three occasions under general anesthesia. The chest CT in our patient showed cystic and collapsed lesions, predominantly in the right lung.…”
Section: Discussioncontrasting
confidence: 57%
“…Although it has been reported that patients in the prone position were better oxygenated than those in the supine position, during general anesthesia [7], our patient experienced low oxygenation in the prone position on three occasions under general anesthesia. The chest CT in our patient showed cystic and collapsed lesions, predominantly in the right lung.…”
Section: Discussioncontrasting
confidence: 57%
“…*p < 0.05 and **p < 0.001 between the supine and prone positions [19,20], alterations in hemodynamics, regional diaphragm movements or lung volumes are no different in the prone position versus the supine position and edema is uniformly distributed [21]. In anesthetized normal prone subjects, diaphragm excursions in non-dependent (dorsal) regions are more pronounced [22] and measured functional residual capacity (FRC) is higher than in supine subjects [23,24]. It is not known, however, if FRC increases in ARDS patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 Physiologic measurements in the patient subgroup with a significant increase in oxygenation after being turned prone (responders) and the subgroup without a significant change in oxygenation after being turned prone (nonresponders). Mean ± SD Prone responders (n = 16) Prone nonresponders (n = 7) Pelosi et al [23] examined the partitioning of the mechanics of the respiratory system into its pulmonary and chest wall components in subjects during general anesthesia. Interestingly, gas exchange and functional residual capacity improved but no positional differences were found in lung and chest wall compliances.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to ventilation, Bryan and Bryan et al [1,6] hypo- Table 1 Clinical characteristics of patients and individual partial pressure of oxygen in arterial blood PaO2/fractional inspired oxygen FIO thesized that ventral decubitus (VD) could enhance expansion and ventilation of the dorsal areas of the lungs, once the patient was placed in a non-dependent position. In fact, Gattinoni et al [7,8] and then Pelosi et al [9,10] documented on computed tomography (CT) the disappearance of lung dorsal densities in ARDS patients placed prone. However, these data were not correlated with respiratory mechanics, and the authors noticed that the CT pattern was similar in both responders and non-responders.…”
Section: Introductionmentioning
confidence: 99%